DR. HERMINA ANGHELESCU: „TREBUIE SĂ GĂSIM SOLUŢII CA SĂ ATRAGEM LA BIBLIOTECĂ PE CEI CARE NU NE TREC PRAGUL...” - MOLDOVAN, Liliana (BIBLIOPOLIS, 2020)
The article is about development of library science education in USA and Romania. The author, Dr H. Angelescu, underlines that the Romanian system must be reformed and mentions that the American program Biblionet, implemented in Romania would help improve the situation.